Role of the hadron molecule Λc(2940) in the pp¯→pD0Λ¯c(2286)annihilation reaction; Physical Review D; Vol. 90, iss. 9 - Yubing Dong; Faessler A.; Gutsche T.; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich (2014, 2014)
Title screen